2014
DOI: 10.2478/s13382-014-0260-1
|View full text |Cite
|
Sign up to set email alerts
|

The risk of subjective symptoms in mobile phone users in Poland – An epidemiological study

Abstract: Objectives: To assess the type and incidence of subjective symptoms related to the use of mobile phones in Polish users. Material and Methods:The study was conducted in 2005 using a questionnaire survey. Although it has been quite a long time, up to now, no such data have been published for Poland. The questionnaire consisted of 53 questions concerning sex, age, education, general health, characteristics of a mobile phone (hand-held, loud-speaking unit) as well as the habits associated with its use (frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 20 publications
4
23
1
6
Order By: Relevance
“…The correlation between mobile phone use and headaches has previously been reported in several studies. Similar to the result of the present study, it has been reported that the headache severity perceived by mobile phone users was greater as the duration of a phone call using a mobile phone was increased [12,34,35]. In addition, it has been reported that the heat sensation adjacent to the ears was increased as the duration of a phone call using a mobile phone was increased [36,37], and a considerable number of the subjects who complained of this heat sensation also complained of headaches [38].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The correlation between mobile phone use and headaches has previously been reported in several studies. Similar to the result of the present study, it has been reported that the headache severity perceived by mobile phone users was greater as the duration of a phone call using a mobile phone was increased [12,34,35]. In addition, it has been reported that the heat sensation adjacent to the ears was increased as the duration of a phone call using a mobile phone was increased [36,37], and a considerable number of the subjects who complained of this heat sensation also complained of headaches [38].…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have suggested that headaches, which are a type of non-specific symptom, might be correlated with mobile phone use [12-14]. This cross-sectional study analyzed the correlations between the characteristics of mobile phone usage (frequency and duration) and symptoms related to daily living, such as headaches, stress, cognitive function, depression, and sleep patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the rapid development and widespread mobile phone use in everyday life (almost 24 hours a day), it is important to study the possible negative health effects [6]. A person addicted to a mobile phone is so absorbed in their phone that they are not able to function normally without it.…”
Section: Introductionmentioning
confidence: 99%
“…Szczegóły doboru osób do grupy i dotyczące samej grupy zamieszczono w publikacji Szyjkowskiej i wsp. (2014) [7]. W dalszym etapie badań z grupy wybrano osoby, które zawodowo korzystały z telefonów komórkowych (208 osób).…”
Section: Materiał I Metodyunclassified
“…W niniejszym badaniu oprócz wrażenia ciepła w okolicy ucha zgłaszano przede wszystkim uczucie znużenia po rozmowie, nawet przyjemnej, zaburzenia pamięci świeżej i pogorszenie koncentracji uwagi [7,18]. W badaniach Hockinga (1998) [19], Khan (2008) [20] oraz Meo i Al-Dress (2005) [21] dominującymi objawami związanymi z używaniem telefonu komórkowego były natomiast bóle głowy, zaburzenia Tabela 7.…”
Section: Omówienieunclassified